2019
DOI: 10.18502/ijhoscr.v13i4.1891
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Association between Androgen Receptor and AURKA and Its Prognostic Value in Gastric Cancer

Abstract: Background: It is well-known that Aurora kinase A (AURKA) shows oncogenic properties in various tumor types including gastric cancer (GC). Moreover, previous studies have demonstrated that AURKA has a specific androgen receptor (AR) binding site in its promoter; thus, it could be regulated by AR. Since it has been shown that AR overexpresses in gastric cancer (GC) as a male-predominant tumor, the goal of this study was to evaluate the association between AR and AURKA and its prognostic value in GC patients. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…For example, Chen et al (2017) suggested that AURKA was reactivated in metastasis of irradiated hepatocellular carcinoma (HCC) through facilitating epithelial–mesenchymal transitions (EMTs) and cancer stem cell (CSC) properties. Soleymani Fard et al (2019) showed that upregulation of AURKA might promote gastric cancer progression. de Jong et al (2019) indicated that a high expression of AURKA correlated with cell cycle progression during chondrosarcoma cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chen et al (2017) suggested that AURKA was reactivated in metastasis of irradiated hepatocellular carcinoma (HCC) through facilitating epithelial–mesenchymal transitions (EMTs) and cancer stem cell (CSC) properties. Soleymani Fard et al (2019) showed that upregulation of AURKA might promote gastric cancer progression. de Jong et al (2019) indicated that a high expression of AURKA correlated with cell cycle progression during chondrosarcoma cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 ZEB1 is abnormally expressed in a variety of cancers, such as colorectal cancer, lung cancer, breast cancer, and gastric cancer, and it is involved in the proliferation, migration and invasion of cancer cells and is considered to have cancer-promoting functions. [32][33][34][35][36] For example, lncRNA TMPO-AS1 facilitates the proliferation, migration, and invasion of cervical cancer cells by modulating the miR-143-3p/ZEB1 axis. 37 In this study, we predicted and verified that miR-484 was able to target ZEB1, and that ZEB1 expression in ccRCC patient tissues was positively regulated by PCED1B-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relevant importance of all kinase targets mentioned before, AURKA has attracted special attention for being an emergent target in gastric cancer therapy and prognosis evaluation. 40 Numerous in vitro, in vivo, and tissue sample studies have shown the involvement of AURKA in gastric cancer development through different types of intracellular pathways. 30,41,42 Several studies also have shown the significant association of AURKA gene F I G U R E 5 Survival fraction of gastric cancer patients enrolled in this study.…”
Section: Discussionmentioning
confidence: 99%